Security Cooperation between China and Russia in the Context of the Emerging Polycentric World Order - Zh. Ji; O. E. Grishin (Проблемы постсоветского пространства)
The article analyzes the key features of Russia-China cooperation in the field of security within the context of the emerging polycentric world order. Amid growing international instability and the escalation of global threats, Russia-China cooperation is becoming increasingly significant as a key factor for ensuring regional and global stability and security. The study focuses on political mutual trust as the cornerstone of stability and examines multifaceted collaboration in areas such as economic, energy, food, and military security. However, Russia-China cooperation faces significant challenges, including international pressure driven by the hegemonic policies of certain Western countries, the deterioration of the global security environment, and economic asymmetries between the two countries. Additionally, diverging regional interests in Central Asia, East Asia, and South Asia may pose obstacles to joint efforts in addressing critical global and regional issues.